Indications for, and timing of, planned caesarean section: A systematic analysis of clinical guidelines. Issue 1 (February 2020) - Coates, Dominiek; Homer, Caroline; Wilson, Alyssa; Deady, Louise; Mason, Elizabeth; Foureur, Maralyn; Henry, Amanda
Abstract: Background: There has been a worldwide rise in planned caesarean sections over recent decades, with significant variations in practice between hospitals and countries. Guidelines are known to influence clinical decision-making and, potentially, unwarranted clinical variation. The aim of this study was to review guidelines for recommendations in relation to the timing and indications for planned caesarean section as well as recommendations around the process of decision-making. Method: A systematic search of national and international English-language guidelines published between 2008 and 2018 was undertaken. Guidelines were reviewed, assessed in terms of quality and extracted independently by two reviewers. Findings: In total, 49 guidelines of varying quality were included. There was consistency between the guidelines in potential indications for caesarean section, although guidelines vary in terms of the level of detail. There was substantial variation in timing of birth, for example recommended timing of caesarean section for women with uncomplicated placenta praevia is between 36 and 39 weeks depending on the guideline. Only 11 guidelines provided detailed guidance on shared decision-making. In general, national-level guidelines from Australia, and overseas, received higher quality ratings than regional guidelines. Conclusion: The majority of guidelines, regardless of their quality, provide very limited information to guide shared decision-making or the timing of planned caesarean section, two of the most vital aspects of guidance. National guidelines were generally of better quality than regional ones, suggesting these should be used as a template where possible and emphasis placed on improving national guidelines and minimising intra-country, regional, variability of guidelines.